Metabolic activity of Sphagnum recurvum under different environmental conditions - Marschall, Marianna; Laufer, Zsanett (Acta Biologica Szegediensis, 2002)
The fate of transgene is an up-to-date question in plant genetic and breeding research. For a breeder, the ability to transfer foreign gene and its Mendelian inheritance is a very important aspect. In crossing experiments the homogenous T2 transgenic line 124 was crossed with different non-transgenic females. The isolated hybrid embryos from the crosses were tested in medium containing bialaphos. This experiment showed the dominant character of bar gene. All the hybrid embryos germinated onto 5mg/l bialaphos medium expressed resistance, while the control variety (GK Góbé) showed sensitivity to the bialaphos as expected. The fertile T1 generation expressed 3:1 segregation ratio for bar +/bar- plants. The transformed foreign gene (bar) was stable in the wheat genome after two self pollinations and PAT asasays. It is therefore, possible to transform transgene successfully via sexual way into non-transgenic genotypes. Cell level selection of bar gene was possible in anther culture. The regenerated haploids and spontaneous diploids were herbicide resistant. Using in vitro haploid technique (anther culture), it’s possible to produce homogenous bar resistant wheat lines by cell-level selection.